Defensive Driving: Directing HIV-1 Vaccine-Induced Humoral Immunity to the Mucosa with Chemokine Adjuvants - Ebony N. Gary; Michele A. Kutzler (Journal of Immunology Research)
A myriad of pathogens gain access to the host via the mucosal route; thus, vaccinations that protect against mucosal pathogens are critical. Pathogens such as HIV, HSV, and influenza enter the host at mucosal sites such as the intestinal, urogenital, and respiratory tracts. All currently licensed vaccines mediate protection by inducing the production of antibodies which can limit pathogen replication at the site of infection. Unfortunately, parenteral vaccination rarely induces the production of an antigen-specific antibody at mucosal surfaces and thus relies on transudation of systemically generated antibody to mucosal surfaces to mediate protection. Mucosa-associated lymphoid tissues (MALTs) consist of a complex network of immune organs and tissues that orchestrate the interaction between the host, commensal microbes, and pathogens at these surfaces. This complexity necessitates strict control of the entry and exit of lymphocytes in the MALT. This control is mediated by chemoattractant chemokines or cytokines which recruit immune cells expressing the cognate receptors and adhesion molecules. Exploiting mucosal chemokine trafficking pathways to mobilize specific subsets of lymphocytes to mucosal tissues in the context of vaccination has improved immunogenicity and efficacy in preclinical models. This review describes the novel use of MALT chemokines as vaccine adjuvants. Specific attention will be placed upon the use of such adjuvants to enhance HIV-specific mucosal humoral immunity in the context of prophylactic vaccination.